Persepsi Dalam Komunikasi Interpersonal - Aswaruddin Aswaruddin; Arimbi Syahkila Simangunsong; Salwa Nabila Damanik; Dina Oktapia; Akbar Rafsanjani (Mathematics Education Study Program, 2025)
This study aims to describe perception in interpersonal communication using a qualitative approach. The data sources used in this study are literature study sources that include references from journals, books and other articles. Perception in interpersonal communication is a complex process that involves how individuals understand, interpret, and give meaning to information received from their social environment. Perception plays an important role in shaping how a person interacts, responds, and builds relationships with others. In the context of interpersonal communication, perception is influenced by various factors, such as personal experience, cultural values, emotions, and stereotypes, all of which can affect the interpretation of messages. The perception process involves the stages of selecting, organizing, and interpreting information, which can result in misperceptions if not accompanied by deep understanding or clear communication. Thus, a proper understanding of perception can help improve the effectiveness of interpersonal communication, encourage empathy, and minimize the potential for conflict in social interactions.